Linking e-Science capabilities for e-Social Science communities: extending the UK-Australia INWA project to the Chinese Academy of Sciences - Lloyd, Ashley; Sun, Yuchao (ESRC National Centre for e-Social Science, 2005)
The INWA Grid project connects grid resources in EPCC (Edinburgh, Scotland), Curtin Business School (Perth, Western Australia) and the Chinese Academy of Sciences (Beijing, China). The project has demonstrated the application of grid computing power to the analysis of distributed data drawn from collaborating companies in each time zone. This data describes regional behaviour within the "e" economy and provides a focus for global eSocial Science collaborations. The infrastructure supporting these interactions however is designed for eScience collaborations and hence differences with the models for global collaborative research within the social sciences, as well as regional differences in access to this infrastructure by the social science community, determine the immediate extent to which global grid technologies can support global eSocial Science. We explore this issue in an examination of the recent evolution of eScience/Grid infrastructure in China as well as broader measures relating to Internet access within China. We observe that some divergence in the uptake of access technologies is already evident within China with potential consequences for future modalities of collaborative social science research in this region.